EVALUASI LAYANAN KEPEGAWAIAN PADA APLIKASI E-MASTER UNTUK TENAGA KEPENDIDIKAN: (Studi pada Cabang Dinas Pendidikan Provinsi Jawa Timur Wilayah Sidoarjo - Kota Surabaya) - Diska Paras Ayu; Supri Hartono; Anggraeny Puspaningtyas (COMMUNITY OF RESEARCH LABORATORY SURABAYA)
Effective and efficient services in today's era cannot be separated from the role of information technology. The implementation of e-Government has become a necessity for an agency to accelerate access and service acceleration. One of them is on BKD Provinsi Jawa Timur that made the eMaster application to bridge staffing services for all ASN in East Java Province. It can't be separated from the teachers and education staff who have just become part of the staffing system at eMaster in 2017. The purpose of this study was to evaluate staffing services on the eMaster application for education personnel in the city of Surabaya. The research method used is descriptive qualitative with data collection through observation and interviews with several eMaster application facilitators at the branch office level and school level. Combining e-Government evaluation theory according to Mason (1978) with public service standards according to Law Number 25 of 2008 concerning public services. The results of this study indicate that the indicators in the evaluation of e-Government include user factors, satisfaction and usability have been applied with several public service standards that have been completed. Furthermore, it is analyzed using the evaluation theory of William. N. Dunn which includes effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. In conclusion, the evaluation of eMaster application services for education personnel has been effective. However, there are some things that need to be addressed in terms of users, both facilitators and the ASN itself.